A prevalence study on the effect of heat stress among a steel plant employees in Selangor Darul Ehsan, 1997 - Sharfudin Noordin,; Jamal Hisham Hashim, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A prevalence study on the acute and chronic symptoms of heat stress was conducted among 306 confirmed male employees of a steel plant in Selangor Darul Ehsan. The respondents were divided into two groups according to the average WBGT of the environmental temperature in the plant. The heat exposed group comprises of respondents working in an average environmental temperature of WBGT 29-35 oC. Whereas the Nonnal group are those respondent working in an average environmental temperature of WBGT 23- 28°C. The questionnaire were based on subjective clinical symptoms experienced by the respondent. Chisquare tests show that there are significant differences between the two groups. For acute symptoms, the heat exposed group reported higher prevalences of subjective symptoms on lethargy (p < 0.001), muscle cramps (p = 0.001), giddiness (p < 0.001), headache (p = 0.010), nausea (p < 0.001) and unstable movement (p < 0.001). The heat exposed group also shows higher clinical symptoms of heat exhaustion (p = 0.001) and heat cramps (p = 0.001). As for chronic symptoms the heat exposed group shows higher subjective symptoms of headache (p = 0.001), giddiness (p = 0.006), irritability (p = 0.011) and palpitation (p < 0.001). This study shows a positive relationship between Nephrolithiasis and hypertension with increasing age of 35 year old. This study also shows a positive relationship between acute symptoms of giddiness and nausea (heat exhaustion), and chronic symptoms of decreased libido and hypertension with increasing body mass index of 4.. In conclusion, changes in environmental temperature do affect the employees' health and attention should be given to control measures.